Untangling the conflation of ‘young adults’ and ‘young people’ in STI and sexual health policy and sex education - Hendry, N.; Brown, Graham; Carman, M.; Ellard, J.; Wallace, J.; Dowsett, G. (Routledge, 2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group Young adults, aged 18–30 years, are disproportionally mentioned in sexually transmissible infection surveillance data both in Australia and internationally. This contributes to categorising young adults as an ‘at risk’ group in health policy. How young adults are framed in policy, and what informs this, have direct implications for policy priorities and responses, including the development of health promotion programmes. In this paper, we provide a case study of Australia’s National Strategies for Blood Borne Viruses and Sexually Transmissible Infections from 2005 to 2017. We identify how ‘young adults’ as a population are masked by, and subsumed within, the broader category of ‘young people’ within these strategies. As a result, young adults become framed by default as a ‘risk category’ that requires education to correct its deficits, regardless of personal experience. For health promotion to advocate, mediate and enable better sexual health outcomes, a policy environment is needed that reflects the changing social and cultural contexts and sexual independence that young adults experience. Sexual health policies should reflect the complexity and opportunities of young adulthood if we are to offer an enabling policy environment for innovative and nuanced health promotion strategies, including adult appropriate health education.